2003
DOI: 10.1590/s1516-93322003000100006
|View full text |Cite
|
Sign up to set email alerts
|

Validação do método de Ducos modificado para a determinação do ácido trans,trans-mucônico urinário

Abstract: O presente trabalho foi realizado objetivando validar um método analítico para a determinação do ácido trans,trans-mucônico (ATTM) urinário empregando-se cromatografia líquida de alta eficiência com detecção UV. O ATTM foi previamente extraído das amostras biológicas, utilizando-se colunas de troca iônica e identificado por cromatografia líquida de alta eficiência (CLAE). O cromatógrafo foi equipado com coluna de fase reversa Lichrosorb RP 18, 5 µm (250 x 4,2 mm). A temperatura da coluna foi mantida a 40 o C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…Moreover, it has been reported that the consumption of alcoholic beverages does not seem to have significantly influenced urinary t,t-MA values [ 10 ]. We have also found no association between levels of urinary t,t-MA and the alcoholic beverages.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, it has been reported that the consumption of alcoholic beverages does not seem to have significantly influenced urinary t,t-MA values [ 10 ]. We have also found no association between levels of urinary t,t-MA and the alcoholic beverages.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of urine creatinine levels were performed after 12 h of collection, by Jaffe’s reaction, as determined by the end-point colorimetric method (Bioclin ® ). All urine samples that presented creatinine values lower than 0.3 g/L or greater than 3.0 g/L were excluded from analysis, following the guidelines of the American Conference of Governmental Industrial Hygienists (ACGIH) [ 10 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Destaca-se ainda que cada cartucho empacotado com o MIP apresentou uma vida útil de até 120 extrações, frente a apenas 3 permitidas pelo método de referência para extração de AttM, a troca iônica. 10,33 A precisão e exatidão intra e interdias foram avaliadas por meio de amostras de urina fortificada com concentração de AttM de 0,5; 3,0 e 7,0 mg L -1 analisadas no mesmo dia (n = 5) e em dias consecutivos (n = 3). Os resultados da precisão intra e interdia são apresentados na forma de desvio padrão relativo e erro relativo, respectivamente (Tabela 3).…”
Section: Figuras De Mérito E Aplicaçõesunclassified